Learning organisation and organisational commitment: evidence in the Vietnamese banking sector. (16th March 2021) - Nguyen, Thi Nguyet Que; Tran, Quan Ha Minh
Despite the vast literature on the relationship between learning organisation and firm performance, very little is known about the extent to which learning organisation contributes to organisational commitment, particularly in the context of transitional economies such as Vietnam. Our study aims to fill out this research gap by shedding new insights about the relative importance of individual dimensions of learning organisation in affecting organisational commitment in the Vietnamese banking sector. We find that all dimensions of learning organisation except inquiry and dialogue, which include continuous learning, inquiry and dialogue, team learning and collaboration, empowerment, embedded system, system connection, and strategic leadership for learning, are the key drivers of organisational commitment. Interestingly, at the organisational level of learning embedded systems, system connection, and strategic leadership are likely stronger drivers of organisational commitment than that of empowerment. Comparisons across all levels of learning suggest that strategic leadership is more important than team learning and collaboration, which is in turn relatively stronger than empowerment, while embedded system is better than continuous learning in contributing to organisational commitment. We discuss the implications for theory and practice, and suggest directions for future research.